Research on the variation of mesh stiffness and transmission error for spur gear with tooth profile modification and wear fault. (April 2021) - Chen, Zhiying; Ji, Pengfei
Highlights: Improved models for mesh stiffness and quasi-static transmission error are proposed. Effects of corner contact and structure coupling are considered to improve models. Analytical calculating processes are built for worn gear pairs with tip relief. Competitive relationship over time between wear and tooth modification is discussed. Abstract: Tooth profile modification and wear are unavoidable, even intentional tooth profile deviations. Both of them have a significant influence on gear mesh stiffness and quasi-static transmission error (QSTE). In this paper, to efficiently and accurately obtain the two internal excitations of spur gear pairs with the above two kinds of deviations together, improved analytical mesh stiffness and QSTE models are proposed. And the effects of corner contact and structure coupling are considered together to overcome the defect of previous works. By comparing with the results of the finite element method, the established models are verified. Through the models, the mesh stiffness and QSTE of the gear pairs with the tooth profile modification and wear simultaneously can be obtained. The results show that both of the two kinds of deviations have significant effects on the limit value and distribution of the mesh stiffness and QSTE. Besides, it can be found that there is a competition between tooth profile modification and wear, and the influence extent of wear is gradually increasing that eventually can override the modification effect. Moreover, wear can affect the selection of tooth profile modification.